Harmonic problems in renewable and sustainable energy systems: A comprehensive review. (December 2021) - Eroğlu, Hasan; Cuce, Erdem; Mert Cuce, Pinar; Gul, Fatih; Iskenderoğlu, Abdulkerim
Abstract: Harmonics are known as distortions in the form of voltage and current, which are driven by the nonlinear loads in the network. Harmonics can be basically asserted as the most common problem in renewable-based power generation technologies. Despite the unequivocal impacts of harmonics on power output and system reliability, it is perspicuous that harmonics generated by renewable energy sources (RES) are not adequately understood and harmonic elimination methods remain underdeveloped. Within the scope of this research the concept of harmonics is evaluated in a thematic way for an easier understanding of the phenomenon. Then, status of harmonic problems in various renewable energy power plants (solar, wind, wave, geothermal, biomass and nuclear) are extensively analysed. Harmonic mitigation and elimination with different control strategies are also discussed in the present work. This review article contributes on presenting an overview of the state-of-the-art harmonics and RES. It is expected that this study will be a source of inspiration for researchers for new studies in the related field.